2003
DOI: 10.1034/j.1600-0447.2003.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of subjective experience in schizophrenia and psychotic bipolar illness

Abstract: These findings, in conjunction with those from other, methodologically similar studies, suggest that certain anomalies of subjective experience aggregate significantly in schizophrenia. These experiential anomalies appear to be relevant for early differential diagnosis and therefore potentially useful in the preonset detection of the schizophrenia spectrum illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
147
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(167 citation statements)
references
References 53 publications
13
147
0
7
Order By: Relevance
“…10 A series of subsequent systematic empirical studies demonstrated that SDs aggregate selectively in first-admission schizophrenia and schizotypal disorders [11][12][13] but not in bipolar psychosis. 14,15 SDs are detectable in populations at high-genetic risk for schizophrenia 13 and are associated with prodromal symptoms among help-seeking, non-psychotic adolescents. 16 SDs predict psychosis in clinically at-risk prodromal populations 17 as well as new cases of schizophreniaspectrum disorders in a follow up of non-spectrum psychiatric patients 5 years after first admission.…”
Section: Introductionmentioning
confidence: 99%
“…10 A series of subsequent systematic empirical studies demonstrated that SDs aggregate selectively in first-admission schizophrenia and schizotypal disorders [11][12][13] but not in bipolar psychosis. 14,15 SDs are detectable in populations at high-genetic risk for schizophrenia 13 and are associated with prodromal symptoms among help-seeking, non-psychotic adolescents. 16 SDs predict psychosis in clinically at-risk prodromal populations 17 as well as new cases of schizophreniaspectrum disorders in a follow up of non-spectrum psychiatric patients 5 years after first admission.…”
Section: Introductionmentioning
confidence: 99%
“… Self-disorders hyper-aggregate in schizophrenia spectrum disorders but not in other mental disorders [39][40][41][42][43]  There is no statistical difference in the level of selfdisorders among patients with schizophrenia and patients with the schizotypal disorder [41,43]  Self-disorders differentiate between first-admitted cases with bipolar psychosis and schizophrenia [42] and self-disorders occur more frequently in residual schizophrenia than in remitted bipolar psychosis [44]  Self-disorders occur in genetically high-risk individuals [45]  Self-disorders are detectable in community samples of adolescent diagnosed as suffering from "at-risk mental state" [46] and in clinical samples of young adults at Clinical High Risk for psychosis [47]  Prospective studies indicate that self-disorders predict transition to psychosis in an Ultra-High Risk for psychosis sample [48] and that high baseline scores of self-disorders predict later transition to a schizophrenia spectrum diagnosis [49,50]  Positive correlations have been found between self-disorders and positive symptoms, negative symptoms, formal thought disorders, and perceptual disturbances, respectively [43]  Correlations have been found between selfdisorders and social dysfunction [51] and suicidality [52,53], respectively  No correlations have been found between selfdisorders and IQ or neurocognitive measures [43,54,55], except for impaired verbal memory [54]  Self-disorders have been found to be temporarily stable over a 5-year period [56] …”
Section: Summary Of Empirical Resultsmentioning
confidence: 99%
“…Badanie z udziałem 151 kolejno przyjętych po raz pierwszy pacjentów o róż-nej diagnozie wykazało, że zaburzenia struktury Ja stanowią ważne aspekty schizofrenii i schizotypii [5,6]. Według jeszcze innego, oddzielnego badania zaburzenia struktury Ja (zarejestrowane w ciągu życia) pozwalają na rozróżnienie pomiędzy schizofrenią rezydualną a psychotyczną chorobą dwubiegunową w remisji [7]. Najnowsze analizy wykazują, że zaburzenia struktury Ja pozwalają połączyć przypadki ze spektrum schizofrenii (schizofrenia i schizotypia) zidentyfikowane na podstawie wyników badania genetycznego rodzin wielopokoleniowych [8].…”
Section: Opracowanie Easeunclassified